One to Two Cycles of Consolidation Chemotherapy With Capecitabine After Neoadjuvant Chemoradiotherapy Does Not Benefit Low-Risk Patients With Locally Advanced Middle-Low Rectal Cancer - Sheng, Xueqing; Li, Shuai; Zhang, Yangzi; Geng, Jianhao; Wang, Hongzhi; Zhu, Xianggao; Quan, Jizhong; Li, Yongheng; Cai, Yong; Wang, Weihu (Frontiers in Oncology, 2021)
Background and Objective: Organ preservation can enable locally advanced rectal cancer (LARC) patients with clinical complete response (cCR) after neoadjuvant treatment to maintain quality of life. In this study, we aimed to evaluate whether one or two cycles of capecitabine after neoadjuvant chemoradiotherapy (NCRT) without extending the interval between the end of NCRT and surgery could increase the complete response (CR) rate in low-risk middle-low LARC patients. Material and Methods: We retrospectively evaluated middle-low LARC patients with low risk defined as clinical T2-3b, mesorectal fascia-clear, and extramural vascular invasion-negative by magnetic resonance imaging (MRI), treated between January 2015 and July 2019. Patients were divided into two groups according to whether consolidation chemotherapy was administered after NCRT. Patients in the consolidation chemotherapy group received one or two cycles of capecitabine (1000 mg/m2 twice daily from days 1 to 14). The main outcome was the CR rate, including pathological CR (pCR) and cCR. Results: A total of 169 patients, 105 in the consolidation chemotherapy group and 64 in the non-consolidation chemotherapy group, were included in the study, and the median follow-up was 37.2 months (range, 0.4–71.2 months). Seventeen patients achieved cCR and the remaining 152 underwent surgery after neoadjuvant treatment. There was no significant difference in the CR rate (39.0% vs. 35.9%, p=0.686), ypT0-2N0 rate (65.2% vs. 63.3%, p=0.812), or ypN0 rate (83.7% vs. 88.3%, p=0.503) between the consolidation chemotherapy and non-consolidation chemotherapy groups. Among the patients achieved cCR, 3 (17.6%) experienced regrowth in the rectum and 2 (11.8%) experienced distant metastasis. There was also no significant difference in the 3-year disease-free survival (87.4% vs 85.9%, p=0.971) in patients who underwent surgery between the two groups. Multivariate logistic regression analysis indicated that normal Carcinoma Embryonic Antigen (CEA) levels (p = 0.001) were associated with a higher CR rate. Moreover, there were no significant differences in the incidences of grade ≥2 acute toxicities during neoadjuvant treatment. Conclusion: Although there was no increase in treatment-related toxicities between the two groups, simply adding one or two cycles of capecitabine after NCRT might be insufficient to benefit low-risk middle-low LARC patients.